Antioxidant And Antiproliferative Activities Of Several Marine Organisms From The West Coast Of Peninsular Malaysia / Chia Yin Yin - Chia, Yin Yin (2016)
Three species of seaweeds (Padina tetrastromatica, Caulerpa racemosa and Turbinaria ornata) and a sponge (Spheciospongia vagabunda) were evaluated for their antioxidant and antiproliferative activities in the human breast adenocarcinoma cell line, MCF-7. The crude extracts of the seaweeds and sponge were sequentially extracted with hexane, dichloromethane, ethyl acetate, acetone and methanol. The extracts showed potent 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical, nitric oxide, superoxide anion and hydroxyl radical scavenging assays. The crude extracts were also evaluated for their antiproliferative effects on MCF-7 cells using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. None of the extracts showed any toxicity in the normal breast cell line, 184B5. The extracts showed antiproliferative activity in MCF-7 cells with half-maximal inhibitory concentration (IC50) of 60.0 – 130.0 μg/ml. The superoxide dismutase (SOD), catalase (CAT) and glutathione reductase (GR) activities in the extracts-treated MCF-7 cells decreased in a dose-dependent manner. Bioassay guided fractionation was conducted on the extract showing the most potent antiproliferative effect. MTT assay was carried out on the partially purified fractions and showed IC50 of 12.0 - 18.0 μg/ml. The most potent fractions were then subjected to liquid chromatography-mass spectrometry (LC-MS) analysis. Camptothecin, pseudopelletierine and lycodine accountable for the cytotoxicity were detected. The IC50 of camptothecin, pseudopelletierine and lycodine were 2.4 ± 2.03, 4.8 ± 1.84 and 6.4 ± 1.97 μg/ml, respectively. It was hypothesised that apoptosis was a mode of cell death by the cancer cells upon treatment. To test this hypothesis, the cellular mechanisms rendering the decreased cancer cell viability were studied. Treatment of MCF-7 cells with the partially purified fractions and pure compounds caused a collapse in the mitochondrial membrane potential (MMP). Caspase-8, -9 and -3 activities increased iv relative to the untreated negative control. Through DNA fragmentation analysis, laddering patterns and fragmentation were observed in the treated MCF-7 cells; further implying that apoptosis was employed as a mechanism of cell death. To further identify and verify the proteins involved in apoptosis, a proteomics approach wasused to study the protein expressions of treated and untreated MCF-7 cells. The methodology involvedtwo dimensional-polyacrylamide gel electrophoresis (2D-PAGE) and Western blotting. The differentially expressed proteins obtained from the 2D gels were analysed usingquadrupole time-of-flight (Q TOF)/LC-MS.A total of 42 proteins were differentially expressed and grouped into 10 biological processes based on their biological functions described in the UniProtKB/Swiss-Prot protein database. Three pro-apoptotic proteins (p53, Bax and PARP-1) were up-regulated while the antiapoptotic protein, Bcl-2, was down-regulated. The fold change in the expression levels of these apoptotic proteins were validated by Western blotting, which were in agreement with the results obtained in 2D-PAGE. In conclusion, exploration of the in vitro pharmacological properties of P. tetrastromatica, C. racemosa, T. ornata and S. vagabunda revealed new possibilities and may represent a new generation of potential drug candidates for the treatment of breast cancer. However, further research in animal models as well as clinical trials are required to ascertain their anticancer properties in vivo, efficacy and safety prior to application in the pharmaceutical industry as natural therapeutic agents.